2021
DOI: 10.1108/gm-01-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

Women’s journey to the top: the role of bonding and bridging social capital

Abstract: Purpose Drawing on Putnam’s concept of social capital, this study aims to examine the oral life histories of women on management boards. It explores how the bridging and bonding forms of social capital are created and used to advance women’s careers to reach top management positions on corporate boards. Design/methodology/approach This study is both explorative and interpretive. A total of 30 semi-structured interviews were conducted with female board members of Polish companies to gain access to their life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
0
13
2
Order By: Relevance
“…Recent studies have provided insights into how career women in Poland and the Republic of Korea use bridging and bonding social capital to achieve career success (Chang et al. , 2021; Górska et al. , 2021).…”
Section: Social Capitalmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have provided insights into how career women in Poland and the Republic of Korea use bridging and bonding social capital to achieve career success (Chang et al. , 2021; Górska et al. , 2021).…”
Section: Social Capitalmentioning
confidence: 99%
“…The study found that the female workers' network that is characterized by intimacy directly leads to career satisfaction among them. Also, Górska et al. (2021) examined how bonding social capital relates to career success among career women on corporate boards in Poland.…”
Section: Bonding Social Capital and Career Successmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of GS as part of other research focused on women's economic and professional advancement. These were mostly conducted with qualitative methods, providing women's views on how GS hinder their professional progress (Górska et al, 2021;Greig & Kudaibergenova, 2019;Kuzhabekova et al, 2018;Kuzhabekova & Almukhambetova, 2019;Mihalčová et al, 2018;Nagy & Primecz, 2014;Nagy & Vicsek, 2014;Tokbayeva, 2020;Turaeva, 2017a).…”
Section: Cemj 65mentioning
confidence: 99%
“…Mihalčová et al (2018) argue that women face gender discrimination in public organizations because of their status as a mother. Górska, et al (2021) ascertain that women business executives link their professional advancement with their supportive family and relatives' egalitarian views. Nagy and Primecz (2014) postulate that women's international managerial careers are positively influenced by their egalitarian spouse and harmed by societal expectations of traditional gender roles.…”
Section: Cemj 65mentioning
confidence: 99%